Growth and yield response of garlic (Allium sativum l.) varieties to nitrogen fertilizer rates at Gantaafeshum, northern Ethiopia - Abadi, T. (Haramaya University, 2015)
Garlic (Allium sativum L.) is one of the most important vegetable crops produced in Tigray region; however, farmers are producing the crop from the available cultivars without or with very low rates of nitrogen fertilizer. The cultivars produced in the region were not evaluated in comparison to improved varieties to the response of nitrogen fertilizer. Therefore, this experiment was conducted during 2014/2015 in Gantaafeshum district in Tigray region with objectives of assessing the effect of nitrogen rates on yield and yield related traits of garlic cultivars and thereby identifying adaptable and high yielding cultivars with higher market demand. Seven garlic cultivars (three improved, three locally introduced and one local) and four N fertilizer rates (0, 41, 82, 123 kg N ha-1) were arranged as 7 x 4 factorial treatments and laid out as a randomized complete block design with three replications. All yield and yield related traits were significantly influenced by the interaction of cultivar and nitrogen fertilizer except leaf length (cm), leaf number per plant, bulb length (cm) and sizes of bulbs and cloves of different categories that were significantly influenced either by both cultivar and nitrogen or one of these. The highest total yield was obtained from the cultivar Bora 1 (12.61 t ha-1) at the rate of 82 kg N ha-1 but the yield decreased to 12.27t ha-1 as the nitrogen level increased to 123 kg N ha-1. The lowest yield was recorded from the local cultivar Guahgot (5.31 t ha-1) without N fertilizer application. The quality was determined based on number of marketable bulbs and weight of cloves.Bora-1 had 44.44 and 20% of bulbs categorized under medium and large categories, respectively. This cultivar had also the highest proportion of marketable cloves categorized under medium (27.10%) and large (33.80%) clove categories. The cost benefit analysis indicated that cultivar Felegdaero followed by Bora 1 both at 41kg N ha-1 rates had maximum marginal economic return of 148.24 and 135.84, respectively. Therefore, it is possible to suggest the advantage of growing cultivar Bora-1 at 82 kg N ha-1followed by Tsedey and Felegdaero varieties both in combination of 123 kg N ha-1at Guahgot, Gantaafeshum district and in other areas having similar agro-ecology.